'Just because we're younger doesn't mean our opinions should be any less valued': A qualitative study of youth perspectives on a Youth Advisory Council in a mental healthcare context - Adrienne Young; Anthony Levitt; Sugy Kodeeswaran; Roula Markoulakis (Wiley, 2023)
Abstract Introduction Recognition of the importance of youth engagement in youth mental health and/or addiction (MHA) service design and delivery is increasing. Youth Advisory Councils embedded in MHA organizations represent one strategy that allows youth to be involved in MHA at the individual, organization and systemic levels. This level of involvement can facilitate positive outcomes for both the youth and the organization. As these councils become more common, it is important that organizations are prepared to partner with the participating youth. This study uses a descriptive qualitative approach to understand the motivations and expectations of youth with lived experience with MHA concerns who were beginning to work on a Youth Advisory Council in an MHA setting in the Greater Toronto Area. Methods Semistructured interviews were conducted with each youth, ages 16-26, on the advisory council (N = 8) to understand their motivations, expectations and goals coming into the work. Interviews were transcribed verbatim and analysed using a reflexive thematic analysis. Results Analysis resulted in five overarching themes: providing opportunities for youth learning and growth, platforming youth, empowering youth, embracing youth leadership and promoting youth‐driven change. The findings illustrate that these youth came into the Youth Advisory Council motivated to create positive change in the mental health system, take on leadership roles and had high expectations for organizational support. Our analyses provide insight for organizations planning and implementing Youth Advisory Councils in the MHA sector with the goal of best supporting youth in driving positive change across the system. Conclusion Youth want to be provided authentic opportunities for their engagement to make a difference. MHA organizations must embrace youth leadership and move towards listening to youth experience and acting on youth recommendations to enhance service design and implementation to improve access and to better meet the needs of youth utilizing these services. Patient or Public Contributions This study incorporated service users, including youth ages 16-26 with lived experience of MHA concerns who served on the Youth Advisory Council at the Family Navigation Project, Sunnybrook. Youth Advisory Council members contributed to two relevant research activities: (1) youth reviewed the draft interview guide before data collection, and their feedback was prioritized in the final version and (2) youth contributed to knowledge translation through contributing to academic conference presentations.